Kesenjangan Harapan antara Pendidik dan Peserta Didik: Analisis dan Solusi - Imroatus Sangaddah; Halimah Halimah; Latifah Istiqomah; Gusmaneli Gusmaneli (Jurnal Pendidikan Sosial Dan Konseling, 2025)
The expectation gap between educators and students is a challenge that impacts the quality of the learning process and outcomes. This expectation gap arises when the goals, perspectives, and learning needs of teachers and students are not aligned, whether in terms of learning methods, communication, learning styles, or the availability of supporting resources. Teachers tend to focus on achieving curriculum and competency targets, while students desire more engaging, relevant learning and support when facing difficulties. This mismatch can result in decreased motivation, low participation, academic stress, and decreased effectiveness of classroom interactions. This study examines the concept of the expectation gap, its causes, and its impact on the learning process. Furthermore, strategies that can be implemented to minimize this gap are discussed, such as two-way communication, learning differentiation, the use of interactive media, improving teacher pedagogical competence, and creating a supportive learning climate. Through a deeper understanding, expectations can be managed so that learning becomes more adaptive, harmonious, and optimally meets student needs.